2010
DOI: 10.1016/j.bbrc.2009.12.040
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation regulates the nuclear mobility of CREB binding protein and its association with nuclear bodies in live cells

Abstract: The lysine acetyltransferase CREB binding protein (CBP) is required for chromatin modification and transcription at many gene promoters. In fixed cells, a large proportion of CBP colocalises to PML or nuclear bodies. Using live cell imaging, we show here that YFP-tagged CBP expressed in HEK293 cells undergoes gradual accumulation in nuclear bodies, some of which are mobile and migrate towards the nuclear envelope. Deletion of a short lysine-rich domain that contains the major SUMO acceptor sites of CBP abrogat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Second, DJ-1 may directly modulate the activity of CBP. The activity of CBP is regulated by posttranslational modification, including sumoylation [70]. Because DJ-1 may inhibit protein sumoylation [18], sumoylation of p300/CBP may be inhibited by nuclear DJ-1.…”
Section: Discussionmentioning
confidence: 99%
“…Second, DJ-1 may directly modulate the activity of CBP. The activity of CBP is regulated by posttranslational modification, including sumoylation [70]. Because DJ-1 may inhibit protein sumoylation [18], sumoylation of p300/CBP may be inhibited by nuclear DJ-1.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in contrast to those reported by Nakayama [20] and might be explained by differences in the cell systems analysed. Furthermore, SUMOylation has been shown to regulate the activity and function of CREB under physiologic conditions [1416]. These data were extended in this study to hypoxia-induced CREB SUMOylation, but its role during hypoxia requires further investigation.…”
Section: Discussionmentioning
confidence: 57%
“…Literature-verified SUMOylation of the 19 potential SUMO-1 targeting TFs are presented in Table 6. The top five potential SUMO TFs, ELK-1 [30], E2F [31], NFY [32], and CREB [33], have all been confirmed to be SUMO substrates by literature review and the percentage of SUMO-verified TFs shown in Figure 6 indicates that the most favorable result is obtained when using the M*C*T combination.…”
Section: Resultsmentioning
confidence: 99%